THE DEVELOPMENT OF LOCATION BASED SERVICES MOBILE APPLICATION FOR PROVIDING HEALTH FACILITIES INFORMATION IN SOUTH JAKARTA - Prasetyo, Dimas Bagus; Wulandari, Lily (Jurnal Ilmiah Informatika Komputer, 2018)
Location based services application for Android devices can help users to know the location of health facilities that are located in South Jakarta area quickly and efficiently. Through smartphone or Android-based mobile devices that have been connected to the Internet network, the user directly treated display a map showing the location of where users are located with a radius as a reference to show the location of the nearest health facilities of the location user. Software development model used to build applications in this research is a prototyping model. The steps taken include planning, data collection, requirement analysis, application design, implementation, and testing. Application testing has been done in two ways, namely using black box testing and user acceptance testing. The testing results of applications using black box testing performed on five Android mobile devices, and the results obtained show that the application can be run properly. Results obtained after rounding is 4.00, so it can be concluded that the user approve this application easy to use and can help in finding information about health facilities.